THE EFFECT OF LEVERAGE, SALES GROWTH AND LIQUIDITY TO THE FIRM VALUE OF REAL ESTATE AND PROPERTY SECTOR IN INDONESIA STOCK EXCHANGE - Febriyanto, Fery Citra (EAJ (Economic and Accounting Journal), 2018)
The value of the firm is essential for the company so as to Determine the factors thataAffect the company into something that needs to be done. This study aims to examine some of the factors that affect the value of the firm are: leverage, sales growth, liquidity, dividend policy, and firm size on firm value of real estate and property in the Indonesia Stock Exchange. This study uses the entire real estate and property company in Indonesia Stock Exchange period of 2011 to 2015, so there are 41 companies as research samples. This study using Tobin's Q to measure the value of the firm. The results Showed that positive leverage effect on the value of the firm due to debt levels are still optimized so that provide positive implications on additional debt. The study of the liquidity variablesshows that liquidity negatively affect the value of the firm due to the value of liquidity are at a maximum. Then the control variable, dividend policy affect the value of the firm and firm size has no effect on the value of firms in the real estate sector and property in the Indonesia Stock Exchange.